Efficient viral delivery of Cas9 into human safe harbor - Hideki Hayashi (Nature Portfolio, 2020)
Abstract Gene editing using CRISPR/Cas9 is a promising method to cure many human genetic diseases. We have developed an efficient system to deliver Cas9 into the adeno-associated virus integration site 1 (AAVS1) locus, known as a safe harbor, using lentivirus and AAV viral vectors, as a step toward future in vivo transduction. First, we introduced Cas9v1 (derived from Streptococcus pyogenes) at random into the genome using a lentiviral vector. Cas9v1 activity was used when the N-terminal 1.9 kb, and C-terminal 2.3 kb fragments of another Cas9v2 (human codon-optimized) were employed sequentially with specific single-guide RNAs (sgRNAs) and homology donors carried by AAV vectors into the AAVS1 locus. Then, Cas9v1 was removed from the genome by another AAV vector containing sgRNA targeting the long terminal repeat of the lentivirus vector. The reconstituted Cas9v2 in the AAVS1 locus was functional and gene editing was efficient.